A note on "zero growth and structural change in a post Keynesian growth model". Issue 1 (2nd January 2020) - Monserand, Antoine
Abstract: This note is a critique of the results found by Rosenbaum concerning zero growth and structural change in a post-Keynesian growth model, some of which are shown to be problematic. First, the (im)possibility for a neo-Kaleckian model of growth and distribution to generate a profit-led growth regime is discussed. Next, we review the role played by the "paradox of costs" when introducing the depreciation of capital and how this changes the stability characteristics of the model presented by Rosenbaum. Finally we show that, contrary to what is claimed in the article, the proposed model is not able to show that zero growth is compatible with a positive net rate of profit.